An In Vitro Study on the Tooth Whitening Capacity of Musa acuminate Peel: A Pilot Study/Marica Jane Sison, Raul Emmanuel Valdez Jr., and Maria Ishtaire P. Quilicot. - Sison, Maricar Jane T., author; Santos, Jessica K.R. ,Course Coordinator and Co-Author.
INTRODUCTION: Various internet articles claim the effectiveness of banana peel
as a whitening agent. An increasing number of testimonials and instructional
materials are spreading online linking potassium, magnesium, and manganese as
responsible agents for tooth whitening. This study determined the whitening
capacity of the inside surface of the banana peel.
METHODOLOGY: An in vitro animal study was done using fifty (50) bovine teeth,
scaled and polished, allocated into 3 treatment groups with different contact time
duration based on the instruction online (2 minutes, 30 minutes, 1 hour) and 2
control groups (Positive control: Crest Whitening application group as per
manufacturer’s instruction; Negative Control: tooth brushing), for 14 days. Baseline
shade and final shade were determined for each tooth by a third-party shade
selector using a Vita Shade Guide system following Munsell Value Chart
RESULTS: Kruskal-Wallis test revealed no significant change in shade apparent
in all treatment groups (p = 0.0057). When compared to the positive control, the
Crest Whitening group revealed a generalized positive (lighter) shade change.
Regardless of the duration of contact time per day between enamel and peel
residue, all 3 treatment groups and the tooth brushing group alone generally
showed no change in tooth shade after 14 days.
CONCLUSION: Banana peel did not lighten the shade of extracted bovine teeth.
Time or contact duration between enamel and banana peel residue did not show
tooth shade changes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Teeth-Bleaching.